2010
DOI: 10.1117/12.844689
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic egomotion computation

Abstract: Computer assistance in Minimally Invasive Surgery is a very active field of research. Many systems designed for Computer Assisted Surgery require information about the instruments' positions and orientations. Our main focus lies on tracking a laparoscopic ultrasound probe to generate 3D ultrasound volumes. State-of-the-art tracking methods such as optical or electromagnetic tracking systems measure pose with respect to a fixed extra-body coordinate system. This causes inaccuracies of the reconstructed ultrasou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2012
2012

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Konen et al [10] suggested an approach for real-time mosaicking for neuro-endoscopic imagery. [11,12] describe a real time endoscopic stitching approach, based on KLT feature tracking, which has been applied to liver EPIs. Finally, an important contribution to this field is the work by Mountney and Yang [13] who suggest a simultaneous loca-tion and mapping approach (SLAM) for the real-time generation of EPIs.…”
Section: Introductionmentioning
confidence: 99%
“…Konen et al [10] suggested an approach for real-time mosaicking for neuro-endoscopic imagery. [11,12] describe a real time endoscopic stitching approach, based on KLT feature tracking, which has been applied to liver EPIs. Finally, an important contribution to this field is the work by Mountney and Yang [13] who suggest a simultaneous loca-tion and mapping approach (SLAM) for the real-time generation of EPIs.…”
Section: Introductionmentioning
confidence: 99%